SELF-HARM DALAM QS. AZ-ZUMAR AYAT 53: PENDEKATAN TAFSIR MAQASHIDI - Mukhtaruddin, Ali Mukmin; Ramadhani, Selsa; Mukmin, Ali; Agustari, Verry; Saputra, Aidil (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Self-harm is a self-harming behavior that is done as a way to relieve emotional distress, although it is not suicidal. It often results from a variety of factors, including an unsupportive social environment and mental health disorders. Thus, this research is important as a form of education and early prevention so that no one commits similar acts. This research aims to examine solutions to self-harm based on the maqasidiy tafsir approach, focusing on QS. Az-Zumar verse 53 which emphasizes Allah's compassion and forgiveness. The research method used is qualitative based on literature study, with data analysis that includes thematic interpretation and maqasidiy interpretation. The results show that humans are not allowed to do self-harm but in reality many do it for self-peace. In addition, this study confirms that Islamic teachings provide a comprehensive solution to the phenomenon of self-harm, by opening the door to spiritual rehabilitation and building hope for individuals experiencing mental health distress.